PENGARUH GOOD PUBLIC GOVERNANCE (GPG) TERHADAP KINERJA GURU EKONOMI SMA/MA NEGERI DI KOTA SALATIGA, KABUPATEN SEMARANG, DAN KOTA SEMARANG DENGAN TEACHER’S WORK ENGAGEMENT (TWE) SEBAGAI VARIABEL INTERVENING - Fahmi Johan Syah, Muhammad (Jurnal Pendidikan Ilmu Sosial, 2016)
The research investigates the influence of good public governance toward economics teacher’s performance in Kota Salatiga, Kabupaten Semarang dan Kota Semarang with teacher’s work engagement as intervening variable. The population of this study is all economics teachers in Kota Salatiga, Kabupaten Semarang and Kota Semarang. Descriptive and path analysis are used to estimate and interpret the results. There are three findings in this research. Firstly, Good Public Governance influences economics teacher’s performance indirectly and totally with teacher’s work engagement as intervening variable. Secondly, economics teacher’s performance is not significantly influenced by good public governance directly. The last finding is that teacher’s work engagement influence economics teacher’s performance directly. On the other words, good public governance increases economics teacher’s work engagement, in doing so influence economics teacher’s performance.